2005
DOI: 10.1002/dvdy.20256
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid generated by Raldh2 in mesoderm is required for mouse dorsal endodermal pancreas development

Abstract: Studies on nonmammalian vertebrate embryos have indicated that retinoic acid (RA) is required for pancreas development. We have analyzed mouse embryos carrying a null mutation of the gene encoding retinaldehyde dehydrogenase 2 (Raldh2), which controls RA synthesis. Raldh2 Ϫ/Ϫ embryos specifically lack expression of Pdx1 (a homeobox gene required for pancreas development) and Prox1 in dorsal endodermal but not ventral endodermal pancreatic precursor tissues. Ventral endodermal expression of Hex is not affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
139
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(151 citation statements)
references
References 34 publications
10
139
0
Order By: Relevance
“…Because we used a relatively high concentration (20%) of serum during EB formation (three-dimensional differentiation), the optimal range of serum concentrations for endodermal differentiation seems to vary depending on the culture conditions. RA generated from lateral plate mesoderm has recently been reported to control Pdx1 expression in early pancreatic development in mice and zebrafish [36][37][38]. Our study demonstrated that RA treatment at the end of EB formation efficiently upregulated PDX1 expression, together with FOXA2 and SOX17 expression, while strongly downregulating the expression of MIXL1 and T, both of which were previously used as markers of the mesendodermal differentiation of ESCs [35].…”
Section: Discussionsupporting
confidence: 59%
“…Because we used a relatively high concentration (20%) of serum during EB formation (three-dimensional differentiation), the optimal range of serum concentrations for endodermal differentiation seems to vary depending on the culture conditions. RA generated from lateral plate mesoderm has recently been reported to control Pdx1 expression in early pancreatic development in mice and zebrafish [36][37][38]. Our study demonstrated that RA treatment at the end of EB formation efficiently upregulated PDX1 expression, together with FOXA2 and SOX17 expression, while strongly downregulating the expression of MIXL1 and T, both of which were previously used as markers of the mesendodermal differentiation of ESCs [35].…”
Section: Discussionsupporting
confidence: 59%
“…The level of conservation in determining pancreatic boundary establishment by Cdx4 and Cyp26a1 across vertebrate species has not been determined. In RALDH2 null mice, which lack a critical RA-synthesizing enzyme, the dorsal pancreas fails to bud and the early glucagon þ cells do not develop (Molotkov et al, 2005;Martin et al, 2005). This dorsal pancreas agenesis phenotype in RALDH2 null mice is reminiscent of the pancreas phenotype observed in Islet1 (Isl1) or N-cadherin (Esni et al, 2001) knockout mice.…”
Section: Figmentioning
confidence: 92%
“…Mouse embryos deficient for the RA-synthesizing enzyme retinaldehyde dehydrogenase 2 (RALDH2), if rescued from early lethality by maternal RA, lack active RA signaling in the foregut region. In the resulting mutants, development of the lungs (Desai et al, 2004;Wang et al, 2006), stomach, duodenum, liver (Wang et al, 2006), and dorsal pancreas (Molotkov et al, 2005) is severely affected.…”
Section: In Vitro Pancreas-induction Systems Using Undifferentiated Xmentioning
confidence: 99%